Penerapan Pola Koordinasi Proteksi Non-Cascade pada OCR Incoming dan OCR Penyulang Trafo - Muhammad Luthfiansyah Romadhoni (Energi & Kelistrikan, 2022)
Reliability is an important aspect to ensure continuity of electrical supply. Fast fault clearing is very important to avoid damaging effects on equipment and power system stability. On the other hand, selectivity of the protection must be achieved to ensure no unnecessary outages. The problem with protection coordination existing is only using delay time between an incoming over-current relay (OCR) and an outgoing OCR to clear the fault in the system. When fault occurs on busbar 20kV, large current will flow through the transformer during fault clearing time. Non-Cascade protection coordination uses simple coordination between incoming OCRs and all outgoing OCRs to determine the exact location of the fault. By using this coordination scheme, Busbar 20 kV fault can be detected, and trip instantly but still gives time to the outgoing relay to trip if the fault occurs on the outgoing.